PENINGKATAN NILAI TAMBAH IKAN BANDENG MENJADI OTAK-OTAK BANDENG DI KELURAHAN TUMENGGUNGAN KECAMATAN LAMONGAN KABUPATEN LAMONGAN - Wachidatus Sa'adah (Universitas Galuh, 2023)
Processed fishery commodities are perishable, so that fast, precise and appropriate handling actions are needed after being caught or harvested. In these conditions, handling and processing actions are needed, one method that can be applied is the milkfish brain processing method. The purpose of this study was to determine the added value of processed milkfish into milkfish brains. The method used in this study is a quantitative method. The results of this study indicate that the added value of milkfish brains is Rp. 30,733.2/kg with a value added ratio of 30.7%.